Pendampingan Penyusunan Rencana Usaha bagi Siswa SMKN 1 Rasau Jaya: Facilitation of Business Plan Preparation for Students of SMKN 1 Rasau Jaya - Yurisinthae, Erlinda; Aritonang, Marisi; Hutajulu, Josua; Yusra, Abdul Hamid A. (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Emerging entrepreneurial interest in Vocational High School students is seen as strategic to prepare future generations who are productive and characterized and able to work in industry, continue their studies, or become creative entrepreneurs. Vocational students who will be entrepreneurs are required to understand financial literacy to have the ability and competence to manage business finances. This community service activity aims to provide training in preparing business plans for students of SMKN 1 Rasau Jaya Rasau Jaya District, Kubu Raya Regency. The implementation of community service follows the preparation, socialization, technology dissemination, evaluation, and reporting stages. The activity of community service was carried out from April to October 2023. In addition to implementing activities, the results of data analysis obtained that 11th-grade students of SMKN 1 Rasau Jaya are interested in entrepreneurs in agriculture and developing agribusiness in Rasau Jaya District. Teachers can encourage interest in entrepreneurship in agriculture among SMKN 1 Rasau Jaya students by inviting successful agribusiness entrepreneurs to disseminate their experiences and motivate students, facilitating students to access resources and funding, and providing students with opportunities for training, demonstrations, and hands-on practice at successful companies/entrepreneurs, collaborating with stakeholders for students to participate in agribusiness competitions and receive recognition for students' innovative ideas, and strengthening the entrepreneurship learning curriculum.